A major crossreactive idiotype associated with human antibodies to the Haemophilus influenzae b polysaccharide. Expression in relation to age and immunoglobulin G subclass. - Lucas, A H (1990)
Using idiotypic analysis, we examined the variable (V) region diversity of human antibodies specific for the capsular polysaccharide of Haemophilus influenzae b (Hib PS). A goat anti-idiotypic serum (anti-Id) was prepared against anti-Hib PS antibodies isolated from the serum of an adult immunized with Hib PS. The anti-Id bound donor anti-Hib PS antibodies and inhibited Hib PS binding of donor anti-Hib PS. In contrast, the anti-Id did not bind donor or pooled Ig depleted of Hib PS antibodies, nor did it inhibit antigen binding of human antibodies to pneumococcal PS's, meningococcal A PS or diphtheria toxoid. Crossreactive idiotype (CRI), as measured by anti-Id inhibition of Hib PS binding, was found in 74 of 98 subjects (76%) vaccinated with Hib PS at 1.7-57 yr of age. 60 of these 74 subjects had greater than 50% of their serum Hib PS-binding activity inhibited by anti-Id. No correlation was found between age and CRI expression. In subjects showing both IgG1 and IgG2 antibody responses, CRI was most frequently detected in both subclasses (71% of subjects). CRI was limited to either IgG1 or IgG2 in 19% of subjects, a finding suggestive of independent B cell lineages. 13 of 15 infants less than 17 mo of age, who responded to Hib PS-outer membrane protein conjugate vaccine, had greater than 50% of their serum anti-Hib PS antibody activity inhibited by anti-Id. The ability of native Hib PS and Hib PS oligomer to partially inhibit (60 and 35%, respectively) the binding between anti-Id and heterologous anti-Hib PS, indicated that some CRI determinants are in or near the combining site. In summary, our findings demonstrate a highly penetrant and frequently predominant CRI, which is expressed in both infants and adults. The results underscore the limited V region diversity of anti-Hib PS antibodies and indicate that CRI predominance is manifest early in ontogeny and is induced by both TI and TD forms of the Hib PS antigen.